2023
DOI: 10.1001/jamanetworkopen.2023.22839
|View full text |Cite
|
Sign up to set email alerts
|

Association of Racial Discrimination With Adiposity in Children and Adolescents

Adolfo G. Cuevas,
Danielle M. Krobath,
Brennan Rhodes-Bratton
et al.

Abstract: ImportanceChildhood obesity is a major public health issue and is disproportionately prevalent among children from minority racial and ethnic groups. Personally mediated racism (commonly referred to as racial discrimination) is a known stressor that has been linked to higher body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) in adults, but little is known about the association of racial discrimination and childhood and adolescent adiposity.ObjectiveTo assess the prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…A recent study found that exposure to racial discrimination was associated with greater adiposity over time in children and adolescents, but research in this domain is lacking. 36 Researchers with expertise in multiple forms of discrimination typically work in fields and departments, such as sociology, that may be disconnected from public health nutrition and medical obesity researchers. Thus, curriculum gaps in SDoO persist at leading nutrition institutions and may be missing from the discussions among stakeholders at national health associations.…”
Section: Methods For Exploratory Student-led Dialogue Sessionsmentioning
confidence: 99%
“…A recent study found that exposure to racial discrimination was associated with greater adiposity over time in children and adolescents, but research in this domain is lacking. 36 Researchers with expertise in multiple forms of discrimination typically work in fields and departments, such as sociology, that may be disconnected from public health nutrition and medical obesity researchers. Thus, curriculum gaps in SDoO persist at leading nutrition institutions and may be missing from the discussions among stakeholders at national health associations.…”
Section: Methods For Exploratory Student-led Dialogue Sessionsmentioning
confidence: 99%